Description in Ibn Jubair’s Journey: An Aanalytical Study in Light of Philip Hāmon’s Techniques - Alreqeb, Shafiq (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aimed at employing Philip Hāmon’s techniques to the study of description in Ibn Jubair’s Journey. Methods: Based on Philip Hāmon’s methods as outlined in his book Du Descriptif, this study took a descriptive and analytical approach. Hamon’s methods focused on the processes of description rather than merely the described object, and they aimed to prepare a poetic or semiotic method of description. Factors including spatial context and the nature and purpose of descriptions were examined. Results: The research found several narrative patterns that contributed to the experience in its way. Formulations often indicate or foretell their inclusion in the text. Different descriptive techniques were used at various points, among the most common were consolidation, designation, defining appearances, rephrasing, and commentary. Ibn Jubair employed several strategies to describe objects, adjusting each one to the context. Analysis showed the Journey’s narration and description are tightly linked. There is no narration independent of description, and the kinetic description often served as narration, to the point where it predominated over the nomadic text. The journey’s description served the recipient’s interests and was built into the description. The ornamental function, the value function, the cognitive function, and the visual function are the most notable of these functions. Conclusions: The research showed that classic writings rely heavily on descriptions to convey both the sights a traveler sees and his emotional response to those sights, and hence there is a need for new studies on modern narrative studies.